Bouncing back: How mothballing curbs prices - Thibaut Duprey; Artur Kotlicki; Daniel E. Rigobon; Philip Schnattinger (Bank of Canada, 2024)
We investigate the macroeconomic impacts of mothballed businesses-those that closed temporarily-on sectoral equilibrium prices after a negative demand shock. First, we introduce a new establishment-level dataset derived from Google Places. We confirm the importance of temporary closures during the COVID-19 pandemic. Data on establishment reviews also suggests that preventing productive businesses from permanently exiting could support employment. Second, we embed these findings into a model of heterogeneous firm dynamics. By maintaining productive capacity during downturns, temporary closures initially support employment and subsequently reduce price pressures. Our results suggest that pandemic fiscal support for temporary closures may have eased inflationary pressures.
Keywords: D22; E32; C55; C81; 330; Central bank research; Firm dynamics; Fiscal policy; Inflation and prices